Human Rights in the Grip of Cultural Relativism: A Critical Examination of Policies and Challenges in Indonesia - John Sinartha Wolo; Bayu Dwi Anggono; Al Khanif; Ahmad Basarah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This paper examines the universal values of human rights and their contradictions within the context of advancing human rights in Indonesia. The Universal Declaration of Human Rights (UDHR) emphasizes the importance of universally respecting human dignity. However, Indonesia, as a country rich in culture and religion, often faces challenges in applying these universal human rights values, particularly when state policies prioritize local cultural considerations over the universal dimension of HR. One example is the prohibition of interfaith marriages, which shows that religious and cultural values still serve as the primary basis in human rights policies in Indonesia. Indonesia is a nation with strong cultural and religious richness, influencing various aspects of life, including state policies related to human rights. Although the UDHR stresses the importance of universal human rights implementation, in practice, Indonesia often experiences tension between these universal values and local values rooted in tradition and religion. This study aims to explore how universal human rights values confront cultural relativism in the Indonesian context, seeking common ground between the two to strengthen the advancement of HR in the country. This study is conducted through an in-depth analysis of literature and relevant scholarly references. The research finds that there is significant tension between human rights universalism and cultural relativism in Indonesia. However, these two approaches have the potential to collaborate and complement each other, with universalism providing a strong normative framework and cultural relativism offering relevant and acceptable local context. These findings are significant as they offer a new perspective in understanding the dynamics of human rights in Indonesia. By considering and integrating these two approaches, human rights policies in Indonesia can be more responsive to local realities without sacrificing fundamental universal principles